Hubungan Sanitasi Kapal Dengan Tanda-Tanda Keberadaan Tikus Pada Kapal Yang Berlabuh Di Pelabuhan Trisakti Banjarmasin - Norhayati Norhayati; Yohanes Joko Supriyadi; M. Irfa'i (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: The Correlation Between Ships Sanitation And The Signs Of The Rats Presence On The Ships That Rest In Trisakti Port Banjarmasin 2017. In accordance with the International Health Regulation (IHR) 2005 and the Regulation of the Minister of Health of the Republic of Indonesia No. 356 of 2008, the Port Health Office is responsible for the port area be rat-free infestation. Ports and ships must be free from the rats presence but data in the ships are find the presence of rats, so it must be fumigation. This study aimed to know the correlation between ships sanitation and the rats presence on ships that rest in Trisakti Port Banjarmasin 2017. This study type was observation in analytic form with cross sectional approach. This samples size were motor boats, tug boat ships, motor vessels and motor tankers, so their total were 20 ships. The instrument used ship sanitation inspection form and rats inspection form. Data analysis used the Fisher Exact Test. Based on the results of statistical test with Fisher Exact Test obtained p-value = 0.017. Thus, p-value count